Mangrove Land Conversion in Indonesia's Coastal Areas - Apriani, Apriani; Delistiani (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Mangrove forests are formations of specific plants, and are generally found growing and developing in protected coastal areas in tropical and subtropical areas. The existence of mangrove forests is very important because it can provide many benefits for human survival, mangrove forests can absorb carbon, prevent sea intrusion, erosion and coastal abrasion, wave dampening, water filtration and become a nursery grown place for several types of animals, especially fish. Objective: This study aims to analyzing land conversion that occurs affects the conversion of mangrove land in coastal areas of Indonesia. Methods: The method used in this study is a literature review study. Literature searches were conducted through the pubmed and google scholar databases using the keyword